HEPATOPROTECTIVE EFFECT OF CHELIDONIUM MAJUS.L EXTRACT AGAINST ANTITUBERCULAR DRUGS INDUCED HEPATIC DAMAGE IN WISTAR RATS. - RUPASRI DUTT-ROY,; KAYALVIZHI E,; MANIKANDAN B,; CHANDRASEKHAR M, (International Journal of Pharma and Bio Sciences, 2015)
The present study was designed to evaluate the hepatoprotective effect of Chelidonium majus L. (Papaveraceae) in Isoniazid and Rifamipicin induced toxicity in wistar rats Material and methods: Four groups, each of six experimental Wistar rats were employed. The control (Group 1) received vehicle treatment, Group II received Rifampicin (RIF) (100 mg/kg, p.o.) and co administered with Isoniazid (INH) (100 mg/kg, p.o) in sterile water. Group III received drug Chelidonium (500mg/kg/p.o/day) and Group IV drug Chelidonium (500mg/kg/p.o/day) along with INH-RIF combination at a dose of (100mg/kg/p.o) of each continued for 21 days. After which rats were sacrificed, blood and liver were taken for biochemical studies, respectively. Liver biomarkers such as alanine aminotransferase (ALT) and aspartate amino transferanse (AST) and Total bilirubin (TB) were elevated on anti-tubercular drugs administration. The treatment of ethanolic extract of C.majus at a dose of 500 mg/kg/p.o with anti-tubercular drugs have significantly reduced liver biomarker enzymes. Antioxidant parameters such as SOD, CAT, GPx and were suppressed and an increase in malondialdehyde (MDA) level were observed due to anti-tubercular drugs administration but restored the liver biomarkers and antioxidant levels in the treatment of ethanolic extract of C.majus. The result of the present study was indicated that C.majus showed a protective effect on hepatotoxicity induced by anti-tubercular drugs. Abbreviations: Alanine Aminotransferase (ALT),Aspartate Amino Transferanse (AST) Total Bilirubin (TB), Chelidonium majus.L (C.majus), superoxide dismutase (SOD), Catalyse (CAT), glutathione peroxidase (GPx) and malodialdehyde (MDA), Isoniazid (INH), and Rifampicin (RIF).